EXPLORING FACEBOOK’S “WHY AM I SEEING THIS AD” FEATURE: MEANINGFUL TRANSPARENCY OR FURTHER OBFUSCATION? - Angus, Daniel; Burgess, Jean; Carah, Nicholas; Hayden, Lauren; Obeid, Abdul (AoIR Selected Papers of Internet Research, 2023)
For more than a decade, digital advertising has been the primary means of funding online content and services. The evolution of digital advertising towards algorithmically targeted advertising, believed to be highly personalized and tailored to the individual, has presented new challenges for public oversight. Whereas previously, public concern centred on the content of ads and their exposure to audiences, the rise of platform-based advertising means focus has shifted to the distribution of ads and how they reach us. In response to public concerns and regulatory pressures, companies such as Meta (the parent of Facebook) have introduced transparency tools for researchers and consumers to ‘explain’ the function of advertising on the platform, including the Ad Library and the “Why Am I Seeing This Ad” feature. Despite being a central feature of Meta’s response towards increasing external scrutiny, little is known about how the WAIST feature works, or how it operates at a population level. In response we offer a description of WAIST data collected at scale, informed from a nationwide citizen data donation project of Facebook advertising. We analyse this data with a view to better understand Meta’s algorithmic advertising system, and to inform questions regarding the sufficiency of WAIST as an algorithmic explanatory mechanism for users.